Application of low-Re turbulence models for flow simulations past underwater vehicle hull forms - Jagadeesh, P; Murali, K (Journal of Naval Architecture and Marine Engineering, 2009)
Minimum power requirement is one of the important design criteria for successful operation of underwater vehicles. CFD based prediction and estimation of power requirement is increasingly carried out in practice. However, reliable prediction depends on suitable turbulence models. This paper presents a comparative assessment of four low Reynolds number (low-Re) k- Îµ models for computation of hydrodynamic forces on underwater vehicle hull forms. The low-Re models are being considered more suitable for underwater axisymmetric bodies due to the following merits (i) they have no wall function approximations, (ii) they could compute low turbulence levels such as in the viscous sub-layer and (iii) they could account for the effect of damped turbulence. The low-Re models used in the present study are namely the models of Abe-Kondoh-Nagano (k- Îµ AKN), Chang-Hsieh-Chen (k- Îµ CHC), Launder-Sharma (k- Îµ LS), and Yang-Shih (k- Îµ YS). It has been found that the k- Îµ AKN low-Re model consistently provided superior performance in predicting the flow characteristics around underwater vehicle hull forms. Keywords: Axisymmetric bodies, autonomous underwater vehicle, CFD, damping functions, low Reynolds k- Îµ models, QUICK scheme doi: 10.3329/jname.v2i1.2029 Journal of Naval Architecture and Marine Engineering 2(1)(2005) 41-54